Enhancing Children’s Speaking Skills through Game-Based Learning - Adhitya, Galant Nanta; Kristiawan, Yohanes Angie; Traesar, Livia; Nurhantoro, Tri Septa; Hapsari, Apriliana (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2026)
This study aims to evaluate the implementation of Game-Based Learning (GBL) to enhance speaking skills and vocabulary acquisition among young EFL learners at Domby Kid’s Hope 1, Yogyakarta. The problem addressed in this study is the low motivation and limited active use of English, particularly in speaking. To address this issue, GBL was implemented through activities like Duduk Senang and Animal Guessing, designed to increase student engagement and reduce anxiety when speaking. The method used was a descriptive qualitative approach, with data collected through pre- and post-tests, classroom observation, and reflective evaluation. The results showed that GBL successfully improved students' ability to recognize and use English vocabulary related to numbers and animals, as well as increased their confidence in speaking. All students showed significant progress after engaging in GBL activities. The implications of this study suggest that GBL can serve as an effective and enjoyable alternative to traditional language teaching, especially in non-formal education settings, and can contribute to the development of more engaging language teaching methodologies for young learners. === Penelitian ini bertujuan untuk mengevaluasi penerapan Game-Based Learning (GBL) dalam meningkatkan keterampilan berbicara dan penguasaan kosakata pada pelajar bahasa Inggris usia dini di Domby Kid’s Hope 1, Yogyakarta. Masalah yang dihadapi adalah rendahnya motivasi belajar dan keterbatasan dalam penggunaan Bahasa Inggris secara aktif, terutama dalam berbicara. Untuk mengatasi hal ini, GBL diterapkan melalui aktivitas permainan seperti Duduk Senang dan Tebak Hewan, yang dirancang untuk meningkatkan keterlibatan siswa dan mengurangi kecemasan saat berbicara. Metode yang digunakan adalah pendekatan deskriptif kualitatif dengan pengumpulan data melalui tes awal dan akhir, observasi, serta evaluasi reflektif. Hasil penelitian menunjukkan bahwa GBL berhasil meningkatkan kemampuan siswa dalam mengenali dan menggunakan kosakata bahasa Inggris terkait angka dan hewan, serta meningkatkan rasa percaya diri dalam berbicara. Semua siswa menunjukkan kemajuan signifikan setelah mengikuti aktivitas GBL. Implikasi dari kegiatan ini menunjukkan bahwa GBL dapat menjadi alternatif yang efektif dan menyenangkan dalam pengajaran Bahasa Inggris, terutama di lingkungan pendidikan non-formal, dan dapat memberikan kontribusi dalam pengembangan metodologi pengajaran bahasa yang lebih menarik bagi pelajar muda.